THE EFFECT OF WORK LIFE BALANCE AND CAREER DEVELOPMENT ON EMPLOYEE ENGAGEMENT-MEDIATED ORGANIZATIONAL COMMITMENT AT JAPANISE DKI RESTAURANT - Sholikhah, Sholikhah; Rachma Dania, Rizki Firdausi; Suryatni, Mukmin; Ashila Tahany, Nasya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
The purpose of this study is to find out the commitment of Japanise DKI Restaurant employees as measured by Work Life Balance, Carer Development and mediated by Employee Engagement. The method used was descriptive and explanatory with a population of 120 respondents and a sample of 104 people was taken randomly and the data was obtained by distributing questionnaires The data obtained was processed with SPSS software, Lisrel and Path analysis. The results of the processing and analysis show that Work Life Balance has a significant effect on Employee Engagement with a path coefficient of 0.402 Career Development has a significant effect on Employee Engagement with a path coefficient of 0.497 Work Life Balance has no significant effect on Organizational Commitment with a path coefficient of -0.038 Career Development has a significant effect on Organizational Commitment with a path coefficient of 0.286 Employee Engagement has a significant effect on Organizational Commitment with a path coefficient of 0.444 Work Life Balance has a significant effect on Organizational Commitment through Employee Engagement with a path coefficient of 0.178 Career Development has a significant effect on Organizational Commitment through Employee Engagement with a path coefficient of 0.221